The genesis of the Bábí-Baháʼí faiths in Shíráz and Fárs - Afnān, Ḥabīb Allāh. (Numen Book Series, 2008)
The Bábí and Baháʾí Faiths represent two of the most important religious movements of modern times. This book relates the story of the evolution of the Bábí-Baháʾí community, beginning with the birth of its founder, Siyyid ʾAlí-Muhammad, known as the Báb, in 1819 and then traced over the next century and a half in the city of his birth, Shíráz. Its author, Mírzá Habíbuʾlláh Afnán, was himself born in the house of the Báb, reared by the widow of the Báb, who shared with him many stories of the Báb's life, then spent nearly a year with Baháʾuʾlláh in the ʾAkka-Haifa area, and some ten years in close proximity to Baháʾuʾlláh's son ʾAbduʾl-Bahá. He served for the next half century as the hereditary custodian of the house of the Báb, and as such was uniquely qualified to tell the story of the Bábí-Baháʾí Faiths in the city of Shíráz in remarkable and moving detail.